Maternal nativity and sleep-related infant injury deaths in New York City. Issue 1 (January 2015) - Chu, Tracy; Hackett, Martine; Simons, Hannah
Abstract Background Half of all births in New York City are to women born outside of the United States whose infant care practices may differ from official recommendations from the American Academy of Pediatrics. These infants have an overall lower infant mortality rate than those of their US-born counterparts. Aims The aims of this study were to examine sleep-related infant injury death, a leading cause of infant mortality, and its risk factors among infants of US-born and foreign-born women in a large, diverse urban area. Study design Data for 344 infant death cases from medical examiner and vital statistics records were analyzed. Rate ratios and 95% CIs, calculated with Poisson regression models, were used to quantify differences in death rates by maternal and infant characteristics. Bivariate and logistic regression analyses were used to examine differences within the sample of sleep-related infant injury deaths. Outcome measures The outcome measures were rate of sleep-related injury death, and behavioral risk factors associated with these deaths: unsafe sleep positioning, bed-sharing, and excess bedding. Results US-born mothers had a sleep-related infant injury death rate that was over three times that of foreign-born mothers, even when controlling for maternal race/ethnicity, education, and age. However, adverse sleep-related practices were not consistently more prevalent among US-born infants in the sample of deaths, even when controlling for those same demographic factors. Conclusions The higher rate of sleep-related infant injury death among infants of US-born mothers may be explained by more complex socio-demographic factors, or factors outside of infant sleep practices.